2012
DOI: 10.1590/s0100-72032012000400006
|View full text |Cite
|
Sign up to set email alerts
|

Gravidez e disfunção lacrimal

Abstract: ResumoOBJETIVO: Verificar a prevalência de disfunção lacrimal em grávidas, comparando-a com a de mulheres não grávidas. Correlacionar achados de diminuição do filme lacrimal com antecedentes obstétricos. MÉTODOS: Foram entrevistadas 150 mulheres grávidas e 150 não grávidas para avaliação da presença de sintomas de secura ocular e antecedentes obstétricos. Os dois grupos foram submetidos ao teste de Schirmer I e a um questionário para sintomas de olho seco. Pacientes com colagenoses, uso de medicamentos associa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 5 publications
0
5
0
1
Order By: Relevance
“…During pregnancy, the body undergoes several physiological hormonal changes which could potentially cause dryness [ 8 ]. Previous research shows that disruption of acinar cells, lacrimal dysfunction, fluctuations in blood glucose levels, and altered tear film physiology and associated ocular surface changes are some of the contributing factors towards dry eye in pregnant women [ 8 – 10 , 28 , 29 ]. While the health care delivery and monitoring systems are well established during pregnancy, the eye care and vision related symptoms are often neglected.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…During pregnancy, the body undergoes several physiological hormonal changes which could potentially cause dryness [ 8 ]. Previous research shows that disruption of acinar cells, lacrimal dysfunction, fluctuations in blood glucose levels, and altered tear film physiology and associated ocular surface changes are some of the contributing factors towards dry eye in pregnant women [ 8 – 10 , 28 , 29 ]. While the health care delivery and monitoring systems are well established during pregnancy, the eye care and vision related symptoms are often neglected.…”
Section: Discussionmentioning
confidence: 99%
“…Studies report that during pregnancy, lacrimal gland growth factor expression can be altered and lacrimal aci-nar cells could be damaged, increasing the risk of dry eye [8,9]. On the other hand, positive objective findings of dry eye among pregnant women with the absence of subjective findings are also reported [10][11][12][13][14]. Women undergo significant emotional and physiological changes during pregnancy [15,16].…”
Section: Introductionmentioning
confidence: 99%
“…The dry eye syndrome secondary to the direct effects on the lacrimal acinar cells of prolactin, transforming growth factor beta 1 (TGF-β1), and epidermal growth factor is found at the level of the lacrimal apparatus [3,5]. Skare et al [8] identified an increased incidence of dry eye syndrome among pregnant women compared to the control group.…”
Section: Ocular Anterior Segment Changes In Pregnancymentioning
confidence: 99%
“…Tear production decreases due to lacrimal dysfunction, resulting in dry eye syndrome [5,6]. Also, corneal sensation is significantly decreased [7][8][9].…”
Section: Physiologic Changesmentioning
confidence: 99%